2007
DOI: 10.1088/0031-9155/52/23/023
|View full text |Cite
|
Sign up to set email alerts
|

Air-kerma determination using a variable-volume cavity ionization chamber standard

Abstract: A graphite-walled cavity ionization chamber of modular design and variable volume has been used to determine the air-kerma rate in the reference 60Co field at the BIPM. The chamber can be configured in five sizes. High-accuracy mechanical measurements of the volume of the air cavity were made for each configuration using a co-ordinate measuring machine. Ionization current measurements were made for each configuration and corrected for the effects of ion recombination and diffusion, stem scatter and chamber ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Combined, these experiments provide a comprehensive set of 60 Co data covering various chamber geometries and wall materials. In a more recent paper, Burns et al 9 reported high-precision measurements but only for a graphite chamber. 9 Based on information in the original papers, schematic diagrams of the chambers used in the above-mentioned studies are shown in Fig.…”
Section: Iia Experimental Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Combined, these experiments provide a comprehensive set of 60 Co data covering various chamber geometries and wall materials. In a more recent paper, Burns et al 9 reported high-precision measurements but only for a graphite chamber. 9 Based on information in the original papers, schematic diagrams of the chambers used in the above-mentioned studies are shown in Fig.…”
Section: Iia Experimental Datamentioning
confidence: 99%
“…In a more recent paper, Burns et al 9 reported high-precision measurements but only for a graphite chamber. 9 Based on information in the original papers, schematic diagrams of the chambers used in the above-mentioned studies are shown in Fig. 1 as they were modeled in this investigation using EGSnrc.…”
Section: Iia Experimental Datamentioning
confidence: 99%
See 3 more Smart Citations